Productivity and species richness in longleaf pine woodlands: resource‐disturbance influences across an edaphic gradient. Issue 9 (September 2016) - Kirkman, L. K.; Giencke, L. M.; Taylor, R. S.; Boring, L. R.; Staudhammer, C. L.; Mitchell, R. J.
Abstract: This study examines the complex feedback mechanisms that regulate a positive relationship between species richness and productivity in a longleaf pine‐wiregrass woodland. Across a natural soil moisture gradient spanning wet‐mesic to xeric conditions, two large scale manipulations over a 10‐yr period were used to determine how limiting resources and fire regulate plant species diversity and productivity at multiple scales. A fully factorial experiment was used to examine productivity and species richness responses to N and water additions. A separate experiment examined standing crop and richness responses to N addition in the presence and absence of fire. Specifically, these manipulations addressed the following questions: (1) How do N and water addition influence annual aboveground net primary productivity of the midstory/overstory and ground cover? (2) How do species richness responses to resource manipulations vary with scale and among functional groups of ground cover species? (3) How does standing crop (including overstory, understory/midstory, and ground cover components) differ between frequently burned and fire excluded plots after a decade without fire? (4) What is the role of fire in regulating species richness responses to N addition? This long‐term study across a soil moisture gradient provides empirical evidence that species richness and productivity in longleaf pine woodlands are strongly regulated by soil moisture. After a decade of treatment, there was an overall species richness decline with N addition, an increase in richness of some functional groups with irrigation, and a substantial decline in species richness with fire exclusion. Changes in species richness in response to treatments were scale‐dependent, occurring primarily at small scales (≤10 m 2 ). Further, with fire exclusion, standing crop of ground cover decreased with N addition and non‐pine understory/midstory increased in wet‐mesic sites. Non‐pine understory/midstory standing crop increased in xeric sites with fire exclusion, but there was no influence of N addition. This study highlights the complexity of interactions among multiple limiting resources, frequent fire, and characteristics of dominant functional groups that link species richness and productivity.